IL-6 and soluble IL-6 receptors (sIL-6R and sgp130) in human pleural effusions: massive IL-6 production independently of underlying diseases - DORÉ, P (Blackwell Science Inc, 1997)
IL-6, soluble IL-6 receptor (sIL-6R) and soluble gp130 (sgp130) levels were measured in sera and pleural effusions from 42 patients with metastatic carcinoma, non-Hodgkin's lymphoma, tuberculosis, cardiac failure and miscellaneous diseases. Pleural IL-6 levels measured by ELISA were very high in all patient groups (mean 34.8 ± 15.3 ng/ml) without significant difference according to diseases. IL-6 was shown to be biologically active in a proliferative assay. Serum IL-6 levels were low (0.049 ± 0.014 ng/ml) and did not correlate with pleural fluid levels. Pleural IL-6 levels correlated with the number of polymorphonuclear cells in pleural fluid (P< 0.03). Pleural sIL-6R levels (76 ± 8 ng/ml) were always lower than serum levels (196 ± 12 ng/ml; P< 0.0001) but correlated with them (P< 0.01). Pleural sIL-6R and albumin levels correlated (P< 0.01), suggesting a transudation of sIL-6R from the serum. Pleural sgp130 levels (10.9 ± 1.0 ng/ml) were lower than serum levels (24.6 ± 2.8 ng/ml; P< 0.002). After gel filtration of pleural fluid, the bulk of IL-6 (>90%) was recovered in a 15 000–30 000 fraction, corresponding to the expected mol. wt of free IL-6. These results suggest a production and a sequestration of IL-6 in the pleural cavity in all studied conditions.